The distinct impact of voluntary and autonomic pelvic floor muscles on genito-pelvic pain/penetration disorder. Issue 4 (2nd October 2019) - Spoelstra, Symen K.; Weijmar Schultz, Willibrord C. M.; Reissing, Elke D.; Borg, Charmaine; Broens, Paul M.A.
ABSTRACT: While the debate on diagnostic distinction continues, the DSM-5 combined dyspareunia and vaginismus into the genito-pelvic pain/penetration disorder. Recent research into the pathophysiology of dyspareunia and vaginismus has focused mainly on general pelvic floor pathology, the experience of pain, and cognitive-affective factors, while ignoring female genito-pelvic reflexes. It has not been taken into account that the vaginal canal, with its surrounding musculature, is an active canal capable of genito-pelvic reflexes, and that several of these reflexes might be triggered separately and/or simultaneously during sexual activity. We hypothesize that vaginal reflexive contractions play a substantial role in the pathogenesis of genito-pelvic pain/penetration disorder and postulate the genito-pelvic reflex hypothesis, i.e. in acute dyspareunia, primarily voluntary contractions or inadequate relaxation of the pelvic floor muscles predominate to guard against the pain due to vaginal trauma/infection and/or stress/anxiety. In chronic dyspareunia, these voluntary contractions induce increasingly submucosal vaginal damage: contact and pain receptors become more sensitive. The increased sensitivity of the contact receptors induces powerful autonomic reflexive contractions. These autonomic contractions provoke vulvar pain, which causes overreactive pelvic floor muscles. In lifelong vaginismus, autonomic reflexive contractions of the pelvic floor muscles predominate the entire disease process.